Brain functional and structural changes in diabetic children. How can intellectual development be optimized in type 1 diabetes? - Maia Stanisławska-Kubiak; Katarzyna Anna Majewska; Agata Krasińska; Paulina Wais; Dominik Majewski; Ewa Mojs; Andrzej Kȩdzia (SAGE Publishing, 2024)
The neuropsychological functioning of people with type 1 diabetes (T1D) is of key importance to the effectiveness of the therapy, which, in its complexity, requires a great deal of knowledge, attention, and commitment. Intellectual limitations make it difficult to achieve the optimal metabolic balance, and a lack of this alignment can contribute to the further deterioration of cognitive functions. The aim of this study was to provide a narrative review of the current state of knowledge regarding the influence of diabetes on brain structure and functions during childhood and also to present possible actions to optimize intellectual development in children with T1D. Scopus, PubMed, and Web of Science databases were searched for relevant literature using selected keywords. The results were summarized using a narrative synthesis. Disturbances in glucose metabolism during childhood may have a lasting negative effect on the development of the brain and related cognitive functions. To optimize intellectual development in children with diabetes, it is essential to prevent disorders of the central nervous system by maintaining peri-normal glycemic levels. Based on the performed literature review, it seems necessary to take additional actions, including repeated neuropsychological evaluation with early detection of any cognitive dysfunctions, followed by the development of individual management strategies and the training of appropriate skills, together with complex, multidirectional environmental support.